A protein interaction map for cell-cell adhesion regulators identifies DUSP23 as a novel phosphatase for β-catenin - Gallegos, Lisa Leon (Sci Rep, 2016)
Cell-cell adhesion is central to morphogenesis and maintenance of epithelial cell state. We previously identified 27 candidate cell-cell adhesion regulatory proteins (CCARPs) whose down-regulation disrupts epithelial cell-cell adhesion during collective migration. Using a protein interaction mapping strategy, we found that 18 CCARPs link to core components of adherens junctions or desmosomes. We further mapped linkages between the CCARPs and other known cell-cell adhesion proteins, including hits from recent screens uncovering novel components of E-cadherin adhesions. Mechanistic studies of one novel CCARP which links to multiple cell-cell adhesion proteins, the phosphatase DUSP23, revealed that it promotes dephosphorylation of β-catenin at Tyr 142 and enhances the interaction between α- and β-catenin. DUSP23 knockdown specifically diminished adhesion to E-cadherin without altering adhesion to fibronectin matrix proteins. Furthermore, DUSP23 knockdown produced “zipper-like” cell-cell adhesions, caused defects in transmission of polarization cues, and reduced coordination during collective migration. Thus, this study identifies multiple novel connections between proteins that regulate cell-cell interactions and provides evidence for a previously unrecognized role for DUSP23 in regulating E-cadherin adherens junctions through promoting the dephosphorylation of β-catenin.